2022
DOI: 10.3390/buildings12122164
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Seismic Performance of Hollow Columns with Fiber Lightweight Aggregate Concrete

Abstract: To study the seismic performance of hollow columns with fiber lightweight aggregate concrete, a quasi-static test on eight hollow columns with fiber lightweight aggregate concrete under lateral low-cycle reversed loading and axial force is presented in this article. The effects of the dosage of plastic-steel fibers (0, 3, 6 and 9 kg/m3, respectively), steel fibers (25, 50 and 75 kg/m3, respectively) and the axial compression ratio (0.4 and 0.6, respectively) on the seismic mechanical properties such as capacit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Correspondingly, the seismic behavior of RHSC SWs needs to be improved to meet the higher requirements [20,21]. The latest research results of scholars at home and abroad showed that adding SF into concrete can effectively improve the seismic performance of RC members, including the RHSC SW [22][23][24]. The seismic behavior of SFRC SW subjected to reversed cyclic loading had been tested by several scholars [3,[25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Correspondingly, the seismic behavior of RHSC SWs needs to be improved to meet the higher requirements [20,21]. The latest research results of scholars at home and abroad showed that adding SF into concrete can effectively improve the seismic performance of RC members, including the RHSC SW [22][23][24]. The seismic behavior of SFRC SW subjected to reversed cyclic loading had been tested by several scholars [3,[25][26][27].…”
Section: Introductionmentioning
confidence: 99%